1992
DOI: 10.1126/science.255.5041.188
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene Tectonics and Paleoseismicity, Southern Cascadia Subduction Zone

Abstract: Holocene deformation indicative of large subduction-zone earthquakes has occurred on two large thrust fault systems in the Humboldt Bay region of northern California. Displaced stratigraphic markers record three offsets of 5 to 7 meters each on the Little Salmon fault during the past 1700 years. Smaller and less frequent Holocene displacements have occurred in the Mad River fault zone. Elsewhere, as many as five episodes of sudden subsidence of marsh peats and fossil forests and uplift of marine terraces are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
134
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(137 citation statements)
references
References 13 publications
(11 reference statements)
2
134
1
Order By: Relevance
“…Its seismicity is mostly located offshore: along the Mendocino Transform Fault (MTF), within the highly deformed Gorda plate, and along the Cascadia Subduction Zone (CSZ) (Figure 1). Paleoseismic evidence of great earthquakes along the CSZ [Atwater, 1987], including radiocarbon dating and several offshore turbidite episodes of deformation in the last 2000 years [Clarke and Carver, 1992], indicate that the CSZ is capable of multiple M8+ earthquakes, as large as M9 [Goldfinger et al, 2008;Satake et al, 1996;Heaton and Hartzell, 1987].…”
Section: Methodsmentioning
confidence: 99%
“…Its seismicity is mostly located offshore: along the Mendocino Transform Fault (MTF), within the highly deformed Gorda plate, and along the Cascadia Subduction Zone (CSZ) (Figure 1). Paleoseismic evidence of great earthquakes along the CSZ [Atwater, 1987], including radiocarbon dating and several offshore turbidite episodes of deformation in the last 2000 years [Clarke and Carver, 1992], indicate that the CSZ is capable of multiple M8+ earthquakes, as large as M9 [Goldfinger et al, 2008;Satake et al, 1996;Heaton and Hartzell, 1987].…”
Section: Methodsmentioning
confidence: 99%
“…Tsunami sand layers exist in coastal bays and wetlands at a number of sites along the Cascadia Margin in the Pacific Northwest (PNW) (Figure 2). These have included tidal marshes at Humboldt Bay, California (Clarke and Carver, 1992), Coos…”
Section: Introductionmentioning
confidence: 99%
“…The McKinleyville fault has experienced an average slip rate 184 of 0.6 ± 0.2 mm/yr over the last ca. 200 ka (Petersen et al, 1996), whilst Clarke and Carver (1992) 185 have reported at least two Holocene slip events, each of which resulted in ca. 3.5 m of dip slip along 186 the McKinleyville fault.…”
Section: Zero Extension Directions and Shear Fracture Orientations 137mentioning
confidence: 99%